BEL312: English for Occupational Purposes / Academy of Language Studies - UiTM, Academy of Language Studies (2012)
This course develops students’ ability to use English with greater confidence and fluency in a range of job-related situations. Tasks and activities suggested for each situation are discipline-based with emphasis on the four language skills of reading, writing, listening and speaking.